Social Support to Teenager Breakfast Behavior (Study at Sidoarjo Islamic State Senior High School) - Angga Satria Prayogo; Muji Sulistyowati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2019)
Background: Breakfast is an important activity for people of all ages, including teenagers, before starting their daily activities. There are many benefits of breakfast that can be felt by the body, but some studies showed that some teens have a poor breakfast habit. Purpose: This research was conducted to analyze the effect of social support on breakfast behavior in teenager in the Sidoarjo Islamic State Senior High School (SHS). Methods: This study was an analytic observational study with cross-sectional. The population of this study were 906 teenagers of 11th and 12th grade who were registered as active students in Sidoarjo Islamic State SHS in 2018/2019, while for the sample were 442 teenagers in that school who were willing to be respondents of the study. The sample was taken through cluster random sampling technique. Results: The results showed that 44.1% of respondents had moderate breakfast behavior and 53.8% of respondents had high social support to have breakfast. Good breakfast behavior tends to be more owned by respondents who have high social support, which is 35.3%. Based on the ordinal regression test results, there is an influence of social support on breakfast behavior in teenagers at Sidoarjo Islamic State SHS with Sig. = 0.011. Parents tend to give big contribution to breakfast behavior in teenagers in Sidoarjo Islamic State SHS, namely giving idea of having breakfast, preparing food for breakfast, telling them to have breakfast, and explaining the importance of having breakfast so that the form of social support from parents already includes emotional, informational, instrumental, and appreciation support. Friends also have a contribution to breakfast behavior in teenagers even though it only includes emotional support (explaining the importance of having breakfast) and informational (explaining the importance of having breakfast). Conclusion: The conclusion of this study is social support from parents and friends can influence breakfast behavior in teenagers in Sidoarjo Islamic State SHS.